2010
DOI: 10.1002/nau.20998
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stromal cell therapy for external urethral sphincter restoration in a rat model of stress urinary incontinence

Abstract: Rat MSCs have the ability to differentiate and skew their phenotype towards smooth and striated muscles, as demonstrated by SMA up-regulation and desmin expression. Periurethral injection of MSCs in an animal model of SUI restored the damaged external urethral sphincter and significantly improved VLPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 39 publications
(43 reference statements)
5
49
1
Order By: Relevance
“…ADSCs were cultured for 24 h in 3.5-cm dishes and then incubated in an adipogenic medium (DMEM-HG with 10% FBS, 0.5 mM isobutylmethylxanthine, 1 μM dexamethasone, 10 μM insulin, 200 μM indomethacin, and 1% penicillin-streptomycin [14]) or in myogenic medium (DMEM-HG with 2% FBS, 1% penicillin-streptomycin, and 1 ng/mL transforming factor-beta 1 [17]). As controls, ADSCs were grown in 3.5-cm dishes with complete media (without supplement).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…ADSCs were cultured for 24 h in 3.5-cm dishes and then incubated in an adipogenic medium (DMEM-HG with 10% FBS, 0.5 mM isobutylmethylxanthine, 1 μM dexamethasone, 10 μM insulin, 200 μM indomethacin, and 1% penicillin-streptomycin [14]) or in myogenic medium (DMEM-HG with 2% FBS, 1% penicillin-streptomycin, and 1 ng/mL transforming factor-beta 1 [17]). As controls, ADSCs were grown in 3.5-cm dishes with complete media (without supplement).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…BMSCs have been used in 4 preclinical studies [46][47][48][49] but not in clinical studies ( Table 1). One of these studies used the SCs for seeding a degradable silk scaffold, which was then implanted as a sling in SUI rats [49].…”
Section: Stem Cellsmentioning
confidence: 99%
“…The Crede technique, employed in 6 SC-SUI studies [19][20][21]46,49,63], is performed manually on an anesthetized animal by applying an increasing external force on the abdomen over the bladder with the experimenter's index finger. Immediately after a leak is visually observed at the urethral meatus, the experimenter lifts his/her finger off, and the peak intravesical pressure, that is, the LPP, is recorded via an intravesical catheter.…”
Section: Functional Assessmentmentioning
confidence: 99%
“…These were essentially preclinical studies that used isolated muscle progenitor cells or ex vivo cultured MSCs from bone marrow (12), fat (13)(14)(15)(16) or cord blood (17). Four Phase I clinical studies have reported the efficacy of MSC in SUI, (18) in the context of a post-prostatectomy (19) feminine SUI after the failure of a first line pelvi-perineal physiotherapy or surgical treatment (20,21).…”
Section: Results Of Svf Injectionsmentioning
confidence: 99%